Standard specification for Electric-Resistance-Welded Carbon and Alloy Steel Mechanical Tubing (American Society of Testing Materials, 2008)
This specification covers electric-resistance-welded carbon and alloy steel tubing for use as mechanical tubing. This specification covers mechanical tubing made from hot- or cold-rolled steel. This specification covers round, square, rectangular, and special shape tubing.